Questionable Research Practices Among Dentists - Urooj Waseem, Shehryar Awan, Khizar Ansar Malik, Danish Javed, Sana Zafar, Fasih Ahmad Khan, Amina Tariq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of the study is to explore the frequency of mal-practicing in terms of giving and accepting honorary authorships among dentists in private dental colleges of Lahore Method: This descriptive crossectional study was conducted to collect data from dentists working in private dental colleges of Lahore regarding plagiarism practices. Three private dental colleges were targeted from where data of 95 dentists was obtained. Data was collected using questionnaire to assess the questionable research practices. Results: Refusal on data sharing with legitimate colleagues was never practiced by majority of participants (46.1%). Addition of author(s) to a research paper who have not contributed in study was sometimes practiced by majority of participants (27.9%). Majority of participants reported that they occasionally accept honorary authorship for which you did not qualify (26.26%). Majority of participants reported that they never demanded any honorary authorship (48.41%). Refusal to give authorship to the person who had worked in the study was never practiced by majority of participants (62.11%). Majority of participants reported that they never submission without taking consent from other authors of a manuscript or grant application (65.26%). Majority of the participants reported that they never do a submission of single manuscript to more than one journals at one time (56.84%). Conclusion: Among dentist, mal-practicing in terms of collaboration and authorship is quite low as compared to in other health professional education as per literature. Keywords: Dental education, Ethical policies, Honorary authorships